LncRNA ELDR promotes bladder cancer malignant progression by regulating the miR-1343-3p/TRIM44 axis - Hu, Xiao; Xie, Tianhang; Xiao, Xiao; Mei, Yuhua (Frontiers in Oncology, 2025)
IntroductionBladder cancer (BCa) is one of the most prevalent genitourinary malignancies with high recurrence worldwide. A lack of reliable prognostic biomarkers and effective therapeutic targets hinders its treatment. Emerging evidence indicates that long noncoding RNAs (lncRNAs) are involved in human cancers, including BCa. While lncRNAs hold enormous promise, their specific roles and mechanisms in BCa remain largely unexplored. Here, we identify the lncRNA ELDR as a pivotal oncogenic driver in BCa.MethodsRT-qPCR was used to analyze the expression patterns of ELDR, miR-1343-3p and TRIM44. CCK-8, colony formation, EdU, and Transwell assays were used to detect the effect of ELDR on cell proliferation, migration, and invasion. The association between ELDR, miR-1343-3p and TRIM44 was analyzed by bioinformatics analysis and dual-luciferase reporter assay. Finally, the role of the ELDR-miR-1343-3p-TRIM44 axis in bladder cancer cell behavior was demonstrated.Results and DiscussionELDR is significantly upregulated in BCa tissues, and its high expression correlates with aggressive clinicopathological features and predicts poor prognosis in BCa patients. Functional experiments demonstrate that ELDR enhances BCa cell proliferation, colony formation, migration, and invasion in vitro and accelerates tumor growth in vivo. Mechanistically, ELDR functions as a competitive endogenous RNA (ceRNA) by sequestering tumor-suppressive miR-1343-3p in the cytoplasm, which consequently leads to the upregulation of the oncogene TRIM44. Our findings unveil the ELDR/miR-1343-3p/TRIM44 axis as a crucial pathway in BCa progression, establishing ELDR as a promising prognostic biomarker and an attractive candidate for the development of targeted therapies.